Asthma-associated variants induce IL33 differential expression through a novel regulatory region - Aneas, Ivy; Decker, Donna C; Howard, Chanie L; Sobreira, Débora R; Sakabe, Noboru J; Blaine, Kelly M; Stein, Michelle M; Hrusch, Cara L; Montefiori, Lindsey E; Tena, Juan; Magnaye, Kevin M; Clay, Selene M; et al. (bioRxiv, 2020)
ABSTRACT Genome-wide association studies (GWAS) have implicated the IL33 locus in asthma, but the underlying mechanisms remain unclear. Here, we identify a 5 kb region within the GWAS-defined segment that acts as a strong regulatory element in vivo and in vitro. Chromatin conformation capture showed that this 5 kb region loops to the IL33 promoter, potentially regulating its expression. Supporting this notion, we show that genotype at an asthma-associated SNP, rs1888909, located within the 5 kb region, is associated with IL33 gene expression in human airway epithelial cells and IL-33 protein expression in human plasma, potentially through differential binding of OCT-1 (POU2F1) to the asthma-risk allele. Our data demonstrate that asthma-associated variants at the IL33 locus mediate allele-specific regulatory activity and IL33 expression, providing a novel mechanism through which a regulatory SNP contributes to genetic risk of asthma. Competing Interest Statement The authors have declared no competing interest.